PENINGKATAN KETERAMPILAN BRANDING UMKM TARAKAN MELALUI PEMANFAATAN TEKNOLOGI DIGITAL DI ERA 4.0 - Arif Fadllullah; Moch. Gilang Elang Perkasa; Alpa Rizky Lubis Triyansyah; Putri Natasya Lisandra; Asriandi Asriandi; Rega Rizkan Azizan (LPPM Universitas Abdurrab, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Tarakan City often face challenges in utilizing branding and technology in the digital era to enhance the competitiveness of their products, including competing with national brands from outside the city. Limited knowledge of effective branding strategies and a lack of understanding in using technology, such as graphic design and social media, are the main obstacles in expanding their marketing reach. Therefore, based on these issues, a community service program was proposed in the form of seminars and workshops focused on improving branding skills through the uses of digital technology. The implementation method was based on the Project Action Plan (PAP), involving several stages: site survey, preparation, seminar and workshop execution, evaluation and implementation, as well as reporting and publication preparation. The results of this activity showed a positive impact, as the capability of MSME actors in Tarakan City increased in utilizing digital technology to create and manage their branding more effectively, as well as gaining skills in using editing software and social media to support their product promotion. The benefits obtained from this activity not only helped Tarakan MSMEs adapt to the challenges and opportunities of the digital era but also expanded their product marketing reach and enhanced their competitiveness in both local and national markets. Overall, this activity contributed to improving the knowledge, skills, and competitiveness of MSMEs in Tarakan City, while supporting sustainable local economic growth.